Effect of habitat degradation on competition, carrying capacity, and species assemblage stability. Issue 15 (17th June 2017) - Calizza, Edoardo; Costantini, Maria Letizia; Careddu, Giulio; Rossi, Loreto
Abstract: Changes in species' trophic niches due to habitat degradation can affect intra‐ and interspecific competition, with implications for biodiversity persistence. Difficulties of measuring species' interactions in the field limit our comprehension of competition outcomes along disturbance gradients. Thus, information on how habitat degradation can destabilize food webs is scarce, hindering predictions regarding responses of multispecies systems to environmental changes. Seagrass ecosystems are undergoing degradation. We address effects of Posidonia oceanica coverage reduction on the trophic organization of a macroinvertebrate community in the Tyrrhenian Sea (Italy), hypothesizing increased trophic generalism, niche overlap among species and thus competition and decreased community stability due to degraded conditions. Census data, isotopic analysis, and Bayesian mixing models were used to quantify the trophic niches of three abundant invertebrate species, and intra‐ and interspecific isotopic and resource‐use similarity across locations differing in seagrass coverage. This allowed the computation of (1) competition strength, with respect to each other and remaining less abundant species and (2) habitat carrying capacity. To explore effects of the spatial scale on the interactions, we considered both individual locations and the entire study area ("'meadow scale"). We observed that community stability and habitat carrying capacity decreased as P. oceanica coverage declined, whereas niche width, similarity of resource use and interspecific competition strength between species increased. Competition was stronger, and stability lower, at the meadow scale than at the location scale. Indirect effects of competition and the spatial compartmentalization of species interactions increased stability. Results emphasized the importance of trophic niche modifications for understanding effects of habitat loss on biodiversity persistence. Calculation of competition coefficients based on isotopic distances is a promising tool for describing competitive interactions in real communities, potentially extendible to any subset of ecological niche axes for which specimens' positions and pairwise distances can be obtained. Abstract : Census and isotopic data of benthic macroinvertebrates were used to quantify the effect of habitat degradation on competition strength and species assemblage stability within a seagrass meadow. Niche width, similarity of resource use, and competition strength between species all increased as seagrass coverage declined, whereas habitat carrying capacity and community stability decreased. Indirect effects of competition and spatial compartmentalization of species interactions increased stability even under degraded conditions.